2014
DOI: 10.1099/vir.0.062059-0
|View full text |Cite
|
Sign up to set email alerts
|

The ORF4b-encoded accessory proteins of Middle East respiratory syndrome coronavirus and two related bat coronaviruses localize to the nucleus and inhibit innate immune signalling

Abstract: The recently emerged Middle East respiratory syndrome coronavirus (MERS-CoV), a betacoronavirus, is associated with severe pneumonia and renal failure. The environmental origin of MERS-CoV is as yet unknown; however, its genome sequence is closely related to those of two bat coronaviruses, named BtCoV-HKU4 and BtCoV-HKU5, which were derived from Chinese bat samples. A hallmark of highly pathogenic respiratory viruses is their ability to evade the innate immune response of the host. CoV accessory proteins, for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
127
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(141 citation statements)
references
References 34 publications
9
127
2
3
Order By: Relevance
“…p3 and p5 have been found in the ERGIC, whereas p4a and p4b display a diffuse cytoplasmic distribution and are also partly localized to the nucleus (Siu et al, 2014), although in another study, p4b was found to localize exclusively to the nucleus (Matthews et al, 2014). Both the p4a and the p4b protein of MERS coronavirus have been shown to be a type-I interferon antagonists (Siu et al, 2014;Matthews et al, 2014;Niemeyer et al, 2013). The p4a is particularly interesting in this context, as it is a Table 7 SARS Co-V ORF9b.…”
Section: Accessory Proteins Of Other Betacoronavirusesmentioning
confidence: 97%
“…p3 and p5 have been found in the ERGIC, whereas p4a and p4b display a diffuse cytoplasmic distribution and are also partly localized to the nucleus (Siu et al, 2014), although in another study, p4b was found to localize exclusively to the nucleus (Matthews et al, 2014). Both the p4a and the p4b protein of MERS coronavirus have been shown to be a type-I interferon antagonists (Siu et al, 2014;Matthews et al, 2014;Niemeyer et al, 2013). The p4a is particularly interesting in this context, as it is a Table 7 SARS Co-V ORF9b.…”
Section: Accessory Proteins Of Other Betacoronavirusesmentioning
confidence: 97%
“…Following nuclear localization, SARS-CoV 3b protein traffics to the outer membrane of mitochondria, where it inhibits the induction of type 1 interferon (IFN) elicited by RIG-I and the mitochondrial antiviral signaling protein (77). Similarly, the 4b proteins of MERS-CoV, bat coronavirus (BtCoV)-HKU4, and BtCoV-HKU5 also localize to the nucleus and inhibit type 1 IFN induction and, less efficiently, NF-ÎșB signaling pathways (78). …”
Section: Relevance Of the Cell Nucleus In Coronavirus Rna Synthesismentioning
confidence: 99%
“…Several downstream open reading frames like ORF3a, ORF3b and ORF6 also antagonize sensing or signaling pathways, or block karyopherin 2 nuclear import [13,21] (Figure 1). MERS-CoV also encodes several luxury functions with interferon antagonism activities, including ORF4a, ORF4b and perhaps ORF5, noting that ORF4b antagonizes phosphodiesterase activity and RNAse L activation [26,27,28,29,30]. However, how the exact underlying mechanisms allow these antagonistic molecules to interfere with the effector molecules that establish an antiviral state, assist in wound repair, or prime and enhance an adaptive immune response, which is critical for clearance, is still under study.…”
Section: Innate Immunity and Coronavirus Infectionsmentioning
confidence: 99%